Zosterops lateralis subsp. investigator Mathews - , Mary (Zenodo, 2011)
Zosterops lateralis investigator Mathews Zosterops lateralis investigator Mathews, 1923a: 153 (New Zealand). Now Zosterops lateralis lateralis (Latham, 1801). See Mees, 1969: 30–70, van Balen, 2008: 467– 468, and Checklist Committee, 2010: 309–310. SYNTYPES: collected at Katikati, 10 m, 37.32S, 175.58E (Times Atlas), Tauranga Harbour, AMNH 701115 , female, 2 August 1914, by Robin Kemp (no. 4690); collected at Lucas Creek, Waitemata, AMNH 701119 , male, 2 March 1915, AMNH 701120 , male, 3 February 1915, AMNH 701121 , female, 27 January 1915, AMNH 701122 , sex?, 25 February 1915, by Robin Kemp (nos. 4796, 4776, 4771, 4794, respectively); collected at Oneroa, Waitemata Co., AMNH 701123 , juvenile sex?, 23 February 1915, by Robin Kemp (no. 4790). All were collected on the North Island, New Zealand. From the Mathews Collection via the Rothschild Collection. COMMENTS: Mathews (1923a: 153) did not designate a type but introduced this name with the following comments: ‘‘The New Zealand form is credited with arriving from Australia and spreading all over New Zealand. When Iredale and I (Mathews and Iredale, 1913) drew up the Reference List of the Birds of New Zealand we noted that all the New Zealand birds were like Tasmanian ones and used the name of the Tasmanian subspecies. The green of the head is becoming more restricted, the grey on the back less, the flanks darker, the breast paler, the black lores more pronounced, the throat scarcely tinged with yellow, the bill longer. Whether these changes have taken place in the last sixty years or not I cannot say, but it is necessary to provide a name to attract attention to the fact that, according to the birds examined a distinct form appears to be evolving. As above noted, only one stage of plumage has been seen, as yet, from New Zealand, viz., the so-called winter plumage.’’ This implies that the changes Mathews envisioned had occurred between 1913 and the 1923 description of investigator . The six specimens from the Mathews Collection listed above were all collected after 1913, on Kemp’s second visit to New Zealand, and I consider them syntypes; by 1914 Mathews had essentially stopped adding specimens to his catalog and none of these syntypes was found there. : Published as part of Mary, 2011, Type Specimens Of Birds In The American Museum Of Natural History Part 9. Passeriformes: Zosteropidae And Meliphagidae, pp. 1-193 in Bulletin of the American Museum of Natural History 2011 (348) on page 29 : {"references": ["Mathews, G. M. 1923 a. The birds of Australia. Vol. 11, pts. 1 - 3. London: H. F. and G. Witherby, 1 - 208, pls. 491 - 508.", "Mees, G. F. 1969. A systematic review of the Indo- Australian Zosteropidae (Part III). Zoologische Verhandelingen 102: 3 - 390.", "van Balen, S. 2008. Family Zosteropidae (whiteeyes). In J. del Hoyo, A. Elliot, and D. Christie (editors), Handbook of birds of the world, vol. 13, Penduline-tits to shrikes: 402 - 485. Barcelona: Lynx Edicions, 879 pp., 60 pls., 536 photographs.", "Checklist Committee. 2010. Checklist of the birds of New Zealand, Norfolk and Macquarie islands, and the Ross Dependency, Antarctica, 4 th ed. Wellington: Te Papa Press, 500 pp., 4 maps.", "Mathews, G. M., and T. Iredale. 1913. A reference list of the birds of New Zealand. Ibis (10) 1: 201 - 263, 402 - 452."]}